HARGA, CITRA MEREK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK VIVO DI KECAMATAN PAYUNG - Dani Dani; Siti Napisah (LPPM STIE PERTIBA Pangkalpinang, 2020)
This study aims to examine the effect of Price, Brand Image, and Promotion on Vivo Brand Smartphone Purchase Decisions by using a survey method. The population used in this study were students of SMA Negeri 1 Payung who used incidental sampling, with a sample of 100 respondents. The results of this study indicate that the effect of price, brand image, and promotion simultaneously proved to have a significant effect on the Vivo Brand Smartphone Purchase Decision in Payung District. Partial test shows (1) that price has no significant effect on purchasing decisions for Vivo brand smartphones in the Payung sub-district.